The perception of senior municipal officials in South Africa regarding the internal audit functions - Mamaile, L. J. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The service protests in municipalities in South Africa have received increased publicity in recent years. Internal audit functions (IAF) have been suggested as one of the ways in which service delivery and municipalities' mandate can be reviewed to improve standards and procedures for financial accountability. Internal audit functions assist local government managers, which includes municipal managers and chief financial officers amongst others, in overseeing and monitoring the financial affairs and accountability processes. The internal audit functions are expected to assist the elected officials, municipal managers, and independent auditors in performing their functions within the municipalities. This study utilised a qualitative research design, using AGSA's reports as a research method, in order to achieve the research objective. This study relied on Auditor General's audit opinions for the period of five years in which the perception of the municipal officials was determined with regard to internal audit functions. This was conducted to examine the perception the municipal officials have on the role and work on internal audit functions in their municipalities. Interviews with the municipal officials were conducted to supplement AGSA's data to provide richer detail regarding the perception the municipal officials have on internal audit functions. The study reveals among others that, majority of the municipal officials in South Africa consider the internal audit functions as useless, not meeting the municipalities' expectations and not adding the expected value, therefore, not taken service serious.
Journal article published in The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Internal audit functions; Local government; Municipalities; Perceptions; Auditing, Internal -- South Africa; Municipal officials and employees -- South Africa; Local government -- South Africa; Municipal government -- South Africa